Whole-House Fire Blanket Protection From Wildland-Urban Interface Fires - Takahashi, Fumiaki (Frontiers in Mechanical Engineering, 2019)
Each year, fires in the wildland-urban interface (WUI)—the place where homes and wildlands meet or intermingle—have caused significant damage to communities. To contribute to firefighter and public safety by reducing the risk of structure ignition, fire blankets for wrapping a whole house have been investigated in the laboratory and prescribed wildland fires. The fire blankets aim to prevent structure ignition (1) by blocking firebrands to enter homes through vulnerable spots (gutters, eaves, vents, broken windows, and roofs); (2) by keeping homes from making direct contact with flames of surrounding combustibles (vegetation, mulch, etc.); and (3) by reflecting thermal radiation from a large fire within close range (adjacent burning houses or surface-to-crown forest fires) for a sustained period of time. In the laboratory experiment, two-layer thin fabric assemblies were able to block up to 92 % of the convective heat and up to 96 % of the radiation (with an aluminized surface). A series of proof-of-concept experiments were conducted by placing instrumented wooden structures, covered with different fire blankets, in various fires in ascending order of size. First, birdhouse-sized boxes were exposed to burning wood pallets in a burn room. Second, wall-and-eaves panels were exposed to prescribed fires climbing up slopes with chaparral vegetation in California. Finally, a cedar shed was placed in the passage of the prescribed head fire in the Pine Barrens in New Jersey. The experiments demonstrated both successful performance and technical limitations of thin fire blankets. The key success factors in protecting the WUI structure are (1) the fire blanket’s heat-blocking capability, (2) endurance under severe heat-exposure high-wind conditions, and (3) proper installation. Additional studies are needed in the areas of advanced material/layer development, blanket deployment methods, and multi-structure protection strategies.